Integrated 18F-T807 Tau PET, Structural MRI, and Plasma Tau in Tauopathy Neurodegenerative Disorders - Li, Cheng-Hsuan; Chen, Ta-Fu; Chiu, Ming-Jang; Yen, Ruoh-Fang; Shih, Ming-Chieh; Lin, Chin-Hsien (Frontiers in Aging Neuroscience, 2021)
Background and Objective: Tau-specific positron emission topography (PET) imaging enables in vivo assessment of Alzheimer's disease (AD). We aimed to investigate its performance in combination with plasma tau levels in patients with non-AD tauopathy. Methods: A total of 47 participants were enrolled, including 10 healthy controls, 16 with tauopathy parkinsonism syndromes (9 with corticobasal syndrome [CBS], 7 with progressive supranuclear palsy [PSP]), 9 with frontotemporal dementia (FTD), 4 with AD, and 8 with Parkinson's disease (PD). All participants underwent clinical assessments, 18F-T807 tau PET, brain MRI, and plasma tau assay. Results: The global cortical standard uptake value ratio (SUVR) of 18F-T807 PET was comparable between PD and control (p = 0.088). The cortical SUVR was significantly higher in AD group (p = 0.002) but was modestly increased in PSP group compared to the PD group (p = 0.044), especially in parietal and pallidal regions. Asymmetric 18F-T807 uptake at the pallidum was noted in patients with CBS and FTD. Cortical tau tracer uptake was associated with increased plasma total tau level (p = 0.016), especially in frontal and parietal regions. Regional tracer uptake was correlated with cortical thinning in patients with CBS and PSP (CBS: r = −0.092, p = 0.025; PSP: r = −0.114, p = 0.015). Conclusions: The 18F-T807 tau tracer uptake was only modestly increased in patients with PSP. Although the cortical tau tracer uptake correlated with regional cortical atrophy and plasma tau levels, a four-repeated tau-specific tracer is needed for future classifying tauopathy parkinsonism syndromes.